1985
DOI: 10.2307/1130474
|View full text |Cite
|
Sign up to set email alerts
|

Do Infants See Emotional Expressions in Static Faces?

Abstract: To determine whether young infants discriminate photographs of different emotions on an affect-relevant basis or on the basis of isolated features unrelated to emotion, groups of 17-, 23-, and 29-week-olds were habituated to slides of 8 women posing either Toothy Angry, Nontoothy Angry, or Nontoothy Smiling facial expressions and were then shown 2 new women in the familiarized expression and in a novel Toothy Smiling expression. At all 3 ages, recovery to the novel Toothy Smiling faces occurred only after habi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
97
2
4

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(108 citation statements)
references
References 19 publications
5
97
2
4
Order By: Relevance
“…Although these results are informative with respect to infants' ability to distinguish among different expressions, they tell us little about infants' ability to extract any meaningful information from the expressions they appear to distinguish (see R. F. Caron, A. J. Caron, & Myers, 1982;Nelson, 1987;Oster, 1981;Walker-Andrews, 1988, 1997. Furthermore, findings from several studies suggest that infants' discrimination of facial expressions is based merely on simple featural differences rather than on the recognition of the affective information (R. F. Caron, A. J. Caron, & Myers, 1985;Oster, 1981; but see Kestenbaum & Nelson, 1990). For example, R. F. Caron et al (1985) found that 4-to 8-month-old infants discriminate "toothy" smiles from closed-mouth smiles and closed-mouth anger, but not from toothy anger.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although these results are informative with respect to infants' ability to distinguish among different expressions, they tell us little about infants' ability to extract any meaningful information from the expressions they appear to distinguish (see R. F. Caron, A. J. Caron, & Myers, 1982;Nelson, 1987;Oster, 1981;Walker-Andrews, 1988, 1997. Furthermore, findings from several studies suggest that infants' discrimination of facial expressions is based merely on simple featural differences rather than on the recognition of the affective information (R. F. Caron, A. J. Caron, & Myers, 1985;Oster, 1981; but see Kestenbaum & Nelson, 1990). For example, R. F. Caron et al (1985) found that 4-to 8-month-old infants discriminate "toothy" smiles from closed-mouth smiles and closed-mouth anger, but not from toothy anger.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, findings from several studies suggest that infants' discrimination of facial expressions is based merely on simple featural differences rather than on the recognition of the affective information (R. F. Caron, A. J. Caron, & Myers, 1985;Oster, 1981; but see Kestenbaum & Nelson, 1990). For example, R. F. Caron et al (1985) found that 4-to 8-month-old infants discriminate "toothy" smiles from closed-mouth smiles and closed-mouth anger, but not from toothy anger.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The dynamic display of facial expressions provides unique temporal information about the expressions that is not available in static displays [26]. Although dynamic characteristics of facial expression are mostly overlooked, a few studies examine its effect on the intensity of emotional expressions and suggest that dynamic characteristics of facial of emotion are necessary for full extraction of emotional information from faces [27][28][29]. In the light of that, the dynamics is important in facilitating the perception of facial expressions.…”
Section: Introductionmentioning
confidence: 99%